Varve microfacies and chronology from a new sediment record of Lake Gościąż (Poland). (1st January 2021) - Bonk, Alicja; Müller, Daniela; Ramisch, Arne; Kramkowski, Mateusz A.; Noryśkiewicz, Agnieszka M.; Sekudewicz, Ilona; Gąsiorowski, Michał; Luberda-Durnaś, Katarzyna; Słowiński, Michał; Schwab, Markus; Tjallingii, Rik; Brauer, Achim; et al.
Abstract: The varved sediment of Lake Gościąż (Central Poland) is one of the most detailed and complete climate archives of the Late Glacial and the Holocene in Central Europe. Here, we present microfacies analyses in combination with μXRF core scanning and a detailed varve chronology of a new and continuous GOS18 sediment record. This record presents six lithozones that mark the most prominent depositional and geochemical changes during the Holocene and Late Glacial. Varve boundaries and five main varve microfacies types were distinguished under petrographic microscope. Analysis provides detailed insights into depositional processes and its changes since the Late Glacial. Microfacies components were used to interpret processes leading to varve formation. A new and independent chronology is obtained by triple varve counting on petrographic thin sections that is complemented by 137 Cs measurements and 14 C AMS dating of terrestrial plant remains. The age-depth model consists of three parts: (1) the upper part (0–520 cm) that is primarily based on varve counting, (2) the middle part (520–758 cm) obtained through age-depth modelling and (3) the lower part (758–1897 cm) developed by varve counting. The bottom of the composite profile coincides with the onset of lacustrine sedimentation in the late Allerød at 12, 834 +134/-233 varve yr BP. The largest shift in geochemistry, expressed by log(Ca/Ti) and log(Si/Ti) ratios show a rapid increase of calcite precipitation and primary productivity at 7940 +112/-168 varve yr BP. Possible triggers for this include local changes in hydrology as the formation of "Na Jazach" system due to the Ruda River development and fluctuations of lake water level. Highlights: Combining varve counting, radiometric methods and age-depth relation modeling. Development of the new chronology for Lake Gościąż, central Poland. Varve microfacies and their environmental implications from Allerød to present time. Detailed insights into depositional processes and abrupt geochemical shifts.